The Content of Whistleblowing Procedures: A Critical Review of Recent Official Guidelines - Vandekerckhove, Wim; Lewis, David (Journal of business ethics, 2012)
There is an increasing recognition of the need to provide ways for people to raise concerns about suspected wrongdoing by promoting internal policies and procedures which offer proper safeguards to actual and potential whistleblowers. Many organisations in both the public and private sectors now have such measures and these display a wide variety of operating modalities: inhouse or outsourced, anonymous/confidential/identified, multi or single tiered, specified or open subject matter, etc. As a result of this development, a number of guidelines and policy documents have been produced by authoritative bodies. This article reviews the following five documents from a management perspective, the first two deal with the principles upon which legislation might be based and the others describing good management practice: the Council of Europe Resolution 1729 (COER); Transparency International 'Recommended Principles for Whistleblowing Legislation' (TI); European Union Article 29 Data Protection Working Party Opinion (EUWP); International Chamber of Commerce 'Guidelines on Whistleblowing' (ICC); and the British Standards Institute' Whistleblowing arrangements Code of Practice 2008 (BSI).